Second Korean Guidelines for the Management of Crohn’s Disease - Jae Jun Park; Suk-Kyun Yang; Byong Duk Ye; Jong Wook Kim; Dong Il Park; Hyuk Yoon; Jong Pil Im; Kang Moon Lee; Sang Nam Yoon; Heeyoung Lee (The Korean Journal of Gastroenterology, 2017)
Crohn’s disease (CD) is a chronic, progressive, and disabling inflammatory bowel disease (IBD) with an uncertain etiopathogenesis. CD can involve any site of the gastrointestinal tract from the mouth to the anus, and is associated with serious complications, such as bowel strictures, perforations, and fistula formation. The incidence and prevalence rates of CD in Korea are still lower compared with those in Western countries, but they have been rapidly increasing during the recent decades. Although there are no definitive curative modalities for CD, various medical and surgical therapies have been applied for the treatment of this disease. Concerning CD management, there have been substantial discrepancies among clinicians according to their personal experience and preference. To suggest recommendable approaches to the diverse problems of CD and to minimize the variations in treatment among physicians, guidelines for the management of CD were first published in 2012 by the IBD Study Group of the Korean Association for the Study of the Intestinal Diseases. These are the revised guidelines based on updated evidence, accumulated since 2012. These guidelines were developed by using mainly adaptation methods, and encompass induction and maintenance treatment of CD, treatment based on disease location, treatment of CD complications, including stricture and fistula, surgical treatment, and prevention of postoperative recurrence. These are the second Korean guidelines for the management of CD and will be continuously revised as new evidence is collected.